2021
DOI: 10.1155/2021/6628671
|View full text |Cite
|
Sign up to set email alerts
|

Development of Two Types of Skin Cancer in a Patient with Systemic Sclerosis: a Case Report and Overview of the Literature

Abstract: Systemic sclerosis (SSc) is an uncommon rheumatic disease in which the underlying main histopathologic feature is a thickening of the skin due to excessive accumulation of collagen in the extracellular tissue. Fibrogenesis, chronic inflammation, and ulceration may eventually promote skin neoplasms. Although nonmelanoma skin cancer (NMSC) is the most frequent type, there have been restricted case reports and case series with skin cancers in SSc patients in the literature. Herein, we describe a 78-year-old woman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…There was a significant increase in ejection fraction and fractional shortening which is usually observed in patients with hypertrophic cardiomyopathy, one of the known cardiac abnormalities observed in SSc patients. Interestingly, we previously found that the Snail Tg skin primed the organ for tumor formation (40), which is consistent with reports indicating that SSc patients are more prone to the development of skin cancer (58).…”
Section: Discussionsupporting
confidence: 91%
“…There was a significant increase in ejection fraction and fractional shortening which is usually observed in patients with hypertrophic cardiomyopathy, one of the known cardiac abnormalities observed in SSc patients. Interestingly, we previously found that the Snail Tg skin primed the organ for tumor formation (40), which is consistent with reports indicating that SSc patients are more prone to the development of skin cancer (58).…”
Section: Discussionsupporting
confidence: 91%
“…Human skin cancer is caused by aberrant cell growth that may invade and spread to other parts of the body. Skin cancer is classified as basal cell carcinoma (BCC), squamous cell carcinoma (SCC), or melanoma (MEL) [3]. The rarest kind, melanoma, is the deadliest owing to metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Basal cell carcinoma (BCC), a malignant tumor with a keratinocyte origin, is a non-melanoma skin cancer (NMSC) with increasing incidence worldwide and has the capacity to develop from a benign lesion (verruca vulgaris) or an inflammatory dermatopathology (such as systemic sclerosis) by develops from the basal cells of the hair follicle or from those found at the level of the inter-follicular epidermis [ 1 , 2 , 3 , 4 ]. In the United States of America (USA), BCC has reached top incidences (an increasing trend paralleling that of skin infections) of as high as 50% of all types of cancers, but with low mortality and high morbidity rates (if it is left untreated for a long period of time) [ 5 , 6 ]; it is one of the most frequent malignant tumors found among the white population [ 7 ], with a lifetime risk of developing such a tumor of approximately 28% for women and as high as 39% for men [ 8 ].…”
Section: Introductionmentioning
confidence: 99%